A Study of the Preface and Translation Criticism of Written on the Edge of Life from the Perspective of Receptive Aesthetics - Zou, Shiyi (Journal of Social Science and Humanities, 2025)
Qian Zhongshu published the essay collection Written on the Edge of Life in 1941, a work widely recognized as a model of scholarly essay writing. The preface, though brief, contains profound philosophical insights and stands as one of the classic prefaces in Chinese literature. In 2003, Zheng Yali published the first complete translation of Written on the Edge of Life by a Chinese translator. Guided by Receptive Aesthetics, this paper interprets Qian Zhongshu’s preface and analyzes Zheng Yali’s translation through a comparative study of the source and target texts. It offers critical insights to serve as a reference for the translation of scholarly essays. Zheng Yali’s translation is generally faithful; however, due to the translator’s limited understanding of certain words and phrases and the failure to integrate anticipatory horizons, some mistranslations occur. When translating scholarly essays with strong academic content, translators should reconstruct the author’s style, reproduce the tone through careful wording, and respond flexibly to the author’s stance. Considerations should also be given to readers’ anticipatory horizons, aesthetic needs, and cultural habits.